LDCs and international division of labour: Some lessons from Japanese experience - Benno Engels (Intereconomics, 1975)
The following contribution represents a critical appraisal of the developing countries' demands for a reform of the existing international division of labour which may help to find a better way of improving their position in the world trade system. It is based on a detailed analysis of the Japanese experiences in West European markets.
Keywords: 330; Foreign Trade